On the Kinetics of Mobile Chernov-Lüders Band Fronts; AIP Conference Proceedings; Vol. 1783 : Advanced Materials with Hierarchical Structure for New Technologies and Reliable Structures 2016 - Danilov V. I. Vladimir Ivanovich (2016, 2016)
Title screen